Delivery of inhibitory signalling via co-crosslinking of FcεRI and FcγRIIB with engineered micro-surfaces as a new therapeutic concept - Alharbi, Waleed S. (2018)
Mast cell and basophil mediators play a major role in the development of immunoglobulin E (IgE)-dependent allergic disorders. One of these mediators is histamine, which is released by activation of inflammatory cells through cross-linking of the high affinity IgE receptor (FcεRI). The current immunotherapies are accompanied by major drawbacks, such as an increase the risk of anaphylaxis and systemic reaction, difficulties in allergen extract standardisation of allergen-specific immunotherapy (SIT), and a small but worrying increase in the incidence of cancer with omalizumab. It is known that co-aggregation of immunoglobulin G (IgG) low-affinity receptor (FcγRIIB) with FceεRI can lead to inhibition of mast cell degranulation, thus inhibiting production of pharmacological mediators. The potential underlying this principle has been highlighted by many approaches published in the literature. In this study, we designed a novel immunotherapy vector that takes advantage of the most recent advances in drug delivery systems using microparticles. This micro-carrier will carry the Fc parts of both IgG and IgE in defined stoichiometric ratios to be directed towards the allergic inflammatory cells (mast cells and basophils). Fcγ receptors have different binding affinities for IgG1, either with high affinity in the case of FcγRI, or low as with FcγRIIB. We engineered mutant IgG-Fc fragments with increased binding affinity for FcγRIIB. These recombinant Fc-genes were successfully transfected, expressed and purified from the cell supernatant of a high yield HEK293- 6E cell line mammalian expression system. To obtain a site-specific conjugation between the recombinant Fc proteins and microparticles, a novel 15 amino acid peptide tag known as Avi-Tag was used. Both particle size and Fc density have an effect on the level of the immune response. On the reporter cell lines derived from the parental RBL-2H3 cell lines (RS-ATL8 and NFAT-DsRed), a 0.5μm particle coated with IgE Fc significantly affected the activation response compared to other particles sizes (1,2 and 6 μm). Cell activation was also affected by the density of IgE Fc, and a lower dilution ratio of added IgE Fc to particles (1:50) showed the highest activation value. Unexpectedly, the preliminary data for the release of histamine from purified human peripheral blood basophils treated with different Fc-particle conjugate formulations did not show any effect for the suggested therapy.